Rationalization of the OECS insurance industry - Venner, K. Dwight (Insurance Association of the Caribbean Inc. [St. Michael]BB, 1996)
Focuses on the global and regional environment as it affects the OECS and outlines the process on which the response should be premised. Approaches the above from the viewpoint of the financial system in general and the insurance industry in particular.